Relationship between Motives for Exercise and Sports Practice and Flow Experiences in Youth: Gender Differences - Jiménez-Torres, Manuel G.; Universidad de Granada (Pontificia Universidad Javeriana, 2011)
In this study we explored the relationship between exercise-sports practice, motives for practice and flow experienced during such activities in a sample of Spanish young adults. 101 participants responded self-reports on exercise-sports practice, motives (Capdevila, 2003) and states of flow (Jackson & Eklund, 2002). The results indicated that, compared to women, physical practice was higher among men, who also showed a higher intrinsic motivation and experienced flow at a higher degree. Flow and intrinsic motives predicted physical practice, whilst extrinsic motives could not predict it. These results point out that promoting enjoyment-related motives and positive subjective experiences such as flow might help in enhancing adherence to exercise and sports among young people.